KAKAWIN UDAYANA MAHÀ WIDYA SEBUAH KAJIAN STRUKTURALISME DINAMIK - Eka Septiawan, I Wayan (Humanis; Volume 7. No. 2. Mei 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Research on the Kakawin Udayana Mahà Widya was motivated by the major reason, the uniqueness of this kakawin compared to others. Previous kakawins mostly use an epic theme, while it used Udayana University as its theme. Issues that discussed in this study include form, function, and meaning. This is coherent with the theory Structuralism Dynamic proposed by Mukarovsky. Methods and techniques that used are: (1) in providing data stage using literature methods, methods of reading and interviews, supported by the recording techniques, (2) in data analysis stage using descriptive analytic methods, supported by deductive and inductive thinking and (3) the presentation of data analysis result stage using informal methods. The result of this research is unfolding the structure that built Kakawin Udayana Mahà Widya both formal structure and narrative structure. Formal structure of Kakawin Udayana Mahà Widya included guru-laghu; wrêtta and matra; canda and gana; larik; bait; pupuh; and sargah. In addition to the formal structure above, the discussion also covered the sounds game alamkara whether sabdàlamkara or arthàlamkara. The discussion of narrative structure of Kakawin Udayana Mahà Widya includes manggala; korpus, and epilog. Moreover, there were discussed narrative sequences, sandhi and continuity devices narrative unit of Kakawin Udayana Mahà Widya. In the analysis of the function of Kakawin Udayana Mahà Widya obtained three functions which include: the function of historical documentation; function of education, and entertainment functions. The implicit meaning in the Kakawin Udayana Mahà Widya is bhakti (loyalty), dedication the writer to his alma mater, the Udayana University.
Keywords: Kakawin, Analysis, Structuralism Dynamic